Kebijakan Luar Negeri Indonesia menghadapi sanksi CAATSA Amerika Serikat Tahun 2017-2022 - Omegadon Rutin Maisi (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
Indonesia faces the threat of sanctions under the Countering America’s Adversaries Through Sanctions Act (CAATSA), enacted by President Donald Trump on August 2, 2017, particularly concerning the procurement of Sukhoi Su-35 fighter jets from Russia. Employing a neorealist theoretical framework that underscores the significance of power distribution and national interests within an anarchic international system, this study analyzes how Indonesia, as a regional actor, responds to external pressures from global hegemonic powers. The findings reveal that Indonesia adopts a wait-and-see strategy as a form of structural adaptation, pursues diversification of defense partners as soft balancing, and bolsters multilateral diplomacy to preserve its bargaining position. This research affirms that, in confronting CAATSA pressures, Indonesia acts as a rational state balancing strategic interests with foreign policy autonomy. The study's outcomes contribute to understanding the dynamics of Indonesia's defense diplomacy amid global geopolitical configurations and the imperative of strategic flexibility in its free and active foreign policy doctrine.